A Range Extension of the Social Wasp Polistes Bahamensis (Hymenoptera: Vespidae) - Starr, Christopher K.; Sewlal, Jo-Anne (International Journal of Bahamian Studies, 2011)
Short report on the discovery of the social wasp polistes Bahamensis located on Great Inagua.